MORPHOLOGY OF EYEBALL AND EYELID EPITHELIAL TUMORS IN DIFFERENT STAGES OF GLAUCOMA. (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
Among ophthalmological diseases, glaucoma is a neurodegenerative disease that leads to a gradual loss of vision, in the pathogenesis of which, along with increased intraocular pressure, morphofunctional changes in the sclera tissue play an important role.  At the same time, the trophic state of the eyelid skin and epithelial structures may change at different stages of glaucoma, creating a morphological basis for the development of epithelial tumors. This issue has been poorly studied in the field of ophthalmology, and its comprehensive morphological analysis is urgent.